2011
DOI: 10.1590/s1806-83242011000200013
|View full text |Cite
|
Sign up to set email alerts
|

Pre-heated dual-cured resin cements: analysis of the degree of conversion and ultimate tensile strength

Abstract: This study evaluated the degree of conversion (DC) and ultimate tensile strength (UTS) of dual-cured resin cements heated to 50º C prior to and during polymerization. Disc-and hourglass-shaped specimens of Rely X ARC (RX) and Variolink II (VII) were obtained using addition silicon molds. The products were manipulated at 25º C or 50º C and were subjected to 3 curing conditions: light-activation through a glass slide or through a pre-cured 2-mm thick resin composite disc, or they were allowed to self-cure (SC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
1
18
0
4
Order By: Relevance
“…Therefore, the research hypothesis was accepted for this product regardless of the activation mode. This finding is in agreement with those of studies that evaluated preheated LAs, 22,23 and demonstrates that the previously shown 24 increased LA monomer conversion and improved mechanical properties do increase bond strength to dentin. Possibly, decreased resin viscosity and high radical mobility were not the only factors contributing to the greater bond strength.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the research hypothesis was accepted for this product regardless of the activation mode. This finding is in agreement with those of studies that evaluated preheated LAs, 22,23 and demonstrates that the previously shown 24 increased LA monomer conversion and improved mechanical properties do increase bond strength to dentin. Possibly, decreased resin viscosity and high radical mobility were not the only factors contributing to the greater bond strength.…”
Section: Discussionsupporting
confidence: 92%
“…However, the thickness of indirect materials interposed during photo-activation is a key factor for light attenuation, and polymerization generally decreases as thickness increases. 12 Some studies employing FTIR or FT-Raman used thick (from 0.5 to 1.0 mm) specimens, 14,19 approximately 10 to 20 times thicker than those used in the adhesive luting of indirect restorations. Furthermore, there is a difference in the behavior of thin films as opposed to bulk specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The resin cements were applied at 25°C or were heated to 37°C or 54°C prior to use with the preheating method used in previous studies . For experimental groups, base and catalyst pastes were equally dispensed on a glass plate laying on a heating stirrer surface (C‐MAG HS 7; IKAMAG, Staufen, Germany) previously set to 37°C and 54°C.…”
Section: Methodsmentioning
confidence: 99%